2014
DOI: 10.4269/ajtmh.13-0446
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Factors Affecting the Growth of Burkholderia pseudomallei in Soil Microcosm

Abstract: Abstract. Burkholderia pseudomallei causes melioidosis, the third most common cause of death from infectious diseases in northeast Thailand. Four physicochemical factors were set so that their values covered the range of the northeast, which is an endemic area. The soil pH was set at pH 4-10, soil salinity was 0.0-5.0% NaCl, total iron was 50-150 mg/kg soil, and carbon to nitrogen ratio (C/N) was 10:1 to 40:1. The experiments were carried out at 37 C, and soil moisture was maintained for 7 days. The number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 37 publications
5
33
1
1
Order By: Relevance
“…This result confirmed our earlier findings that these conditions could be used to control bacterial numbers. 16 Our results are consistent with the results of previous studies showing that B. pseudomallei undergoes a transition from a rod form to a coccoid form in response to environmental FIGURE 5. Culturability and viability of Burkholderia pseudomallei grown in soil microcosms supplemented with 1.5% NaCl.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This result confirmed our earlier findings that these conditions could be used to control bacterial numbers. 16 Our results are consistent with the results of previous studies showing that B. pseudomallei undergoes a transition from a rod form to a coccoid form in response to environmental FIGURE 5. Culturability and viability of Burkholderia pseudomallei grown in soil microcosms supplemented with 1.5% NaCl.…”
Section: Discussionsupporting
confidence: 83%
“…The adaptation of B. pseudomallei through morphological alterations may increase its longevity in soil, particularly in endemic areas in which the soil has physicochemical properties suitable for soil-borne pathogens. 16,17,32 Conversely, the loss of culturability and viability observed in soils with high-osmotic stress (i.e., 1.5-3% NaCl), Figure 5A and B) suggests a method of controlling the B. pseudomallei population because our results showed that B. pseudomallei lost its viability after 120 days of exposure to osmotic stress. This result confirmed our earlier findings that these conditions could be used to control bacterial numbers.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations